Epinephrine penetrates through gingival sulcus unlike keratinized gingiva and evokes remote vasoconstriction in human - János Vág; Bernadett Gánti; Barbara Mikecs; Enikő Szabó; Bálint Molnár; Zsolt Lohinai (BMC, 2020)
Abstract Background It has been demonstrated in non-oral tissues that the locally evoked vasoconstriction could elicit remote vasoconstriction. This study aimed to investigate the spreading vasoconstrictor effects of epinephrine in the gingiva. Methods Gingival blood flow (GBF) was measured by laser speckle contrast imager in 21 healthy volunteers. In group A, two wells were fabricated from orthodontic elastic ligature and placed 2 mm apically to the free gingival margin at the mid buccal line of 12 (test side) and 21 (control side) teeth. The GBF was measured in the wells and tightly apical, coronal, distal and mesial to the wells. In group B, the wells were made on the buccal surface of the same teeth, including the gingival sulcus. Four regions were selected for measurement from the gingival margin reaching the mucogingival line (coronal, midway1, midway2 and apical). After the baseline recording, 3 µg epinephrine was applied into the test, and physiological saline into the control well. The GBF was recorded for 14 min. The gingival thickness was measured with a PIROP Ultrasonic Biometer. Results In group A, the GBF did not increase or decrease after the application of epinephrine. In group B, the GBF significantly decreased in all regions of the test side and remained low for the observation period. The vasoconstriction appeared with delays in more apical regions (at min 1 in the coronal and the midway1, at min 2 in the midway2, at min 4 in the apical region). Similarly, the amount of the decrease at 14 min was the largest close to sulcus (− 53 ± 2.9%), followed by the midway1 (− 51 ± 2.8%) and midway2 (− 42 ± 4.2%) and was the lowest in the apical region (− 32 ± 5.8%). No correlation was found between GBF and gingival thickness. Conclusion Epinephrine could evoke intense vasoconstriction propagating to the mucogingival junction, indicating the presence of spreading vasoconstriction in the human gingiva. The attached gingiva is impermeable to epinephrine, unlike the gingival sulcus. This trial was registered in ClinicalTrials.gov titled as Evidence of Spreading Vasoconstriction in Human Gingiva with the reference number of NCT04131283 on 16 October 2019. https://clinicaltrials.gov/show/NCT04131283